Estate Taxation - Tomer Blumkin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper we examine the properties of the optimal linearestate tax in the presence of a complete set of tax instrumentsavailable to the social planner. We allow for both types of bequestmotives, namely altruistic and accidental. We examine the casefor estate taxation which seems to be the strongest (but notimpeccable) with accidental bequests. In general, the estate tax ishighly sensitive to the relative importance of the two bequestmotives.
Keywords: 330